Long-term Oncologic Outcomes After Curative Surgery in Stage I–III Thai Colorectal Cancer Patients - Mongkhonsupphawan A. (2023)
Objective: The survival rate for colorectal cancer varies and there are limited reports regarding the long-term outcomes after curative treatment in Thai patients. This study aimed to determine the long-term oncologic results in non-metastatic Thai colorectal cancer patients after curative surgery. Materials and Methods: We performed a retrospective review of a prospectively collected colorectal cancer registry. Short-term and long-term outcomes were analyzed. Results: 626 patients were included in the study, 51.9% colon cancer and 48.1% rectal cancer patients. The mean age was 63.6 ± 12.7 years. The median follow-up time was 5.4 years [IQR: 2.1–7.4]. The 5-year local recurrence was 6.4%; 3.3% in colon cancer and 9.9% in rectal cancer. The 5-year overall survival (5-yr OS) in the colon cancer patients was 76.3%; 94.6% in stage I, 80.8% in stage II, and 65.3% in stage III. The 5-yr OS in the rectal cancer patients was 65.1%; 84.7% in stage I, 75% in stage II, and 51% in stage III. The 5-year disease-free survival (5-yr DFS) in the colon cancer patients was 76.5%; 91.4% in stage I, 81.3% in stage II, and 66.4% in stage III. The 5-yr DFS in the rectal cancer patients was 63.8%; 81.5% in stage I, 75.1% in stage II, and 50.1% in stage III. Conclusion: The long-term oncologic outcomes after curative treatments in this study were acceptable. The prognosis of treatment depends on the disease stage. Comparing stage by stage, colon cancer has a better prognosis than rectal cancer.